Mekanisme Penggunaan Akad Murabahah Dalam Pembiayaan Pemilikan Rumah Pada PT. Bank Syariah Indonesia KC Tangerang Ciledug : The mechanism of using the Murabahah contract in financing home ownership at PT. Bank Syariah Indonesia KC Tangerang Ciledug - Putri, Intan Febriana; Alawi, Tassyah; Putri, Pebryanti Ananda (Jurnal Mnajemen | Ekonomi | Akuntansi, 2026)
This study aims to analyze the mechanism of murabahah contract implementation in home ownership financing at PT BSI KC Tangerang Ciledug. Murabahah is a sale and purchase contract that discloses the acquisition price and profit margin agreed upon between the seller and the buyer. Sharia-based home financing has become an alternative for Muslim communities who wish to conduct transactions in accordance with Islamic principles. This research employs a descriptive qualitative method with data collection techniques through interviews, observation, and documentation studies. Primary data was obtained through interviews with Account Officers and operational staff, while secondary data was obtained from internal bank documents, DSN-MUI fatwas, and related regulations. The research findings indicate that BSI KC Tangerang Ciledug offers two main home financing products using murabahah contract: BSI Griya Hasanah for commercial property financing and BSI KPR Sejahtera for subsidized housing for Low-Income Communities. The murabahah contract mechanism follows sharia sale and purchase principles with structured stages including customer needs identification, wakalah process, transparent price and margin determination, execution of sale and purchase contract, and fixed installment payments. The implementation of murabahah contract complies with DSN-MUI Fatwa Number 04/DSN-MUI/IV/2000 by applying the principles of price transparency, margin certainty, and fairness for both parties.